2019
DOI: 10.35706/eltinfc.v2i1.2024
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Grammar Mastery and Critical Thinking towards Student’s Descriptive Writing Skill

Abstract: The purpose of this research wants to know the effect both grammar mastery and critical thinking towards student’s descriptive writing skill. It wants to know the effect of grammar mastery towards student’s descriptive writing skill. And then, it wants to know the effect of critical thinking towards student’s descriptive writing skill. Research method is a survey research which is taken from 90 students that are chosen randomly sampling technique at private senior high school in Karawang. There are several ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
1
3
0
1
Order By: Relevance
“…It can be said that the students' CTS level determined the effect of the teaching model used by the lecturer on the students' grammar competence. This study result completed the former studies finding that there was a positive relationship between CTS and the students' English writing ability (Murtadho, 2021;Puspitaloka, 2019;Subroto and Rosalinah, 2017). Besides, this present study result also completed the study by Aditiara et al (2019) indicated that CTS and the students' reading ability had a positive correlation.…”
Section: Discussionsupporting
confidence: 79%
“…It can be said that the students' CTS level determined the effect of the teaching model used by the lecturer on the students' grammar competence. This study result completed the former studies finding that there was a positive relationship between CTS and the students' English writing ability (Murtadho, 2021;Puspitaloka, 2019;Subroto and Rosalinah, 2017). Besides, this present study result also completed the study by Aditiara et al (2019) indicated that CTS and the students' reading ability had a positive correlation.…”
Section: Discussionsupporting
confidence: 79%
“…Purwani (2021)claimed that grammar mastery will make things easier to communicate in English. Moreover, Puspitaloka (2019) highlighted that grammar is one of the key components of learning English and without it, it is difficult to efficiently use the target language learned for both written and oral communication. Shen (2012) demonstrates the importance of grammar in language learning, that all languages have grammar, and each language has its own grammar.…”
Section: Grammar Masterymentioning
confidence: 99%
“…Grammar mastery is significant in choosing the right words to be used in sentences. In addition, grammar mastery has a significant impact on students' descriptive writing and oral communication abilities (Puspitaloka, 2019).…”
Section: A Students' Grammar Skillsmentioning
confidence: 99%